Design of blended board game using neuro linguistic programming (NLP) technique - Burhanuddin Bin Mohd Noor (2023)
The common problem that people been having is stress. The best way to manage the stress have been identified is the combination of NLP, EFT, colour theraphy, Hypnosis and Siva Method.